The Performance of Islamic Stocks and Conventional Stocks During the COVID-19 Shock: Evidence from Indonesian Stock Market - Mohamad Rahmawan Arifin; Ahmad Syahrul Fauzi; Sri Runtiningsih; Frank Aligarh; Arif Nugroho (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This study aims to analyze the performance of Islamic stocks and conventional stocks in Indonesia during the crisis period due to the COVID-19 pandemic. Islamic stocks and conventional stocks are divided based on sharia compliance qualifications by each stock. The sample used in this study is nine sharia stocks taken from the Jakarta Islamic Index (JII) and nine conventional stocks taken based on nine non-shariah compliance stocks included in the IDX30 Index during 31 August 2020 to 31 July. 2022. The analytical method used in this study is Ordinary Least Square (OLS) using panel data, then this study also uses an interaction variable between the three COVID-19 indicators and the sharia compliance variable which represents company compliance with Islamic principles. The estimation results show that daily confirmed cases of COVID-19 and stringency index have a significant negative effect on stock returns in Indonesia, while daily confirmed deaths due to COVID-19 has no effect on stock returns. Furthermore, the results of the interaction between the COVID-19 indicator measures and the sharia compliance variable show that Islamic stocks show greater performance in crises during the COVID-19 pandemic.